Screening for Anti-Inflammation Quality Markers of Lianhua Qingwen Capsule Based on Network Pharmacology, UPLC, and Biological Activity - Zhou, Yongfeng; Niu, Ming; Zhang, Dingkun; Liu, Zhenxing; Wu, Qinghua; Chen, Jiang; Zhang, Haizhu; Zhang, Ping; Pei, Jin (Frontiers in Pharmacology, 2021)
Influenza is a common respiratory infectious disease. In China, Lianhua Qingwen capsule (LHQWC), a drug with significant clinical efficacy and few side effects, is commonly used to treat influenza. However, the composition of LHQWC is complicated, and currently used quality control methods cannot ensure its consistency. In this study, combined with its clinical efficacy, the targets of LHQWC were screened using network pharmacology. Then, anti-inflammation quality markers of LHQWC were screened and judged by combined chemical with biological evaluation. Cyclooxygenase-2 (COX-2) was identified as one of the main targets of the anti-inflammatory activity of LHQWC. The rate of inhibition of COX-2 by different batches of LHQWC was determined. Furthermore, seven components of LHQWC were identified. The potential quality markers were screened by spectral-effect relationship. As a result, chlorogenic acid, isochlorogenic acid B, and isochlorogenic acid C were identified and confirmed as anti-inflammatory quality markers of LHQWC. We hope that these findings provide a scientific basis for the accurate quality control of LHQWC and serve as a reference for the quality control of other drugs.